Application of Listening to Asmaul Husna to Anxiety in Pulmonary Tubercolosis Patients "Case Study" - Ekayanti Hafida Ahmad; Ricky Zainuddin; Nurbaiti Nurbaiti; Yantimala Mahmud; Harun H. Lanipo (Journal La Medihealtico, 2022)
Pulmonary tuberculosis is one of the infectious diseases that has become a global health problem and causes a variety of adverse health effects, including psychological factors such as poor socioeconomic conditions, lack of social support, and decreased quality of life due to a diagnosis that causes anxiety in the majority of pulmonary TB patients. Consequently, proper treatment measures are required to limit the prevalence of pulmonary tuberculosis and its potential consequences. This research intends to investigate the effect of listening to Asmaul Husna on anxiety in patients with pulmonary tuberculosis at Makassar's TK II Pelamonia Hospital. The descriptive technique is a case study of two individuals with pulmonary tuberculosis who meet the following criteria: age > 20 years, Muslim, first 3 months of therapy, willingness to be responders, and excellent orientation. Using a smartphone, patients hear 99 names or traits of Allah that are beneficial for treating the ailment 1 time each day for 10 to 15 minutes. The data were descriptively examined and provided in tabular format. The first responder reported mild anxiety both before and after hearing the Asmaul Husna on the first day of the visit, whereas the second respondent experienced moderate anxiety both before and after hearing the Asmaul Husna. On the second day, the degree of anxiety experienced by the first respondent remained the same as on the first day (moderate scale), however the level of anxiety experienced by the second respondent dropped or eliminated after hearing Asmaul Husna.